Modernisasi Lembaga Pendidikan Islam Non Formal: Studi Fenomenologi pada Madrasah Diniyah Takmiliyah Awaliyah - Ardat Ardat; Haidir Haidir; Khairuddin YM (Prodi PAI STAI Sumatera Medan, 2022)
Madrasah diniyah takmiliyah Awaliyah (MDTA) is often considered a non-formal Islamic educational institution that still maintains the classical system. However, changing times seem to be inevitable and must be accepted by MDTA. In this regard, this study aims to analyze the modernization of education carried out by madrasah diniyah takmiliyah. This research is devoted to MDTA Pendidikan Agama Islam Medan, on the grounds that the madrasa has modernized. The research method used is qualitative based on phenomenological studies. Research informants consisted of madrasa heads and teachers. The results of the study explain that teachers' perceptions of the modernization of madrasah diniyah takmiliyah education should be carried out while respecting traditional and religious values. The aim is to produce graduates who have a balance between religious knowledge, skills, and an understanding of the modern world. Some aspects that are being modernized are a balanced curriculum, teaching methods that are more interactive and inclusive, teacher development, the use of educational technology in learning, evaluation of current learning, collaboration with educational institutions, character education, openness and inclusiveness.